Physical and thermal properties of corn cob powder blended mud cup (khulad) - TUSHIR, SURYA; CHANDRASEKAR, V; TYAGI, S K; MANN, SANDEEP (The Indian Journal of Agricultural Sciences, 2021)
Physical properties and thermal properties of corn cob powder blended mud cups were measured for assessing the feasibility of partial replacement of mud by corn cob powder as an agro biomass utilization process. Corn cob was collected from the fields of Ludhiana district (Punjab, India) and further work was carried out at ICAR-CIPHET, Ludhiana during 2019. The corn cob powder (5, 10 and 15%, g/g) blended mud cups were prepared by baking the molded cups in a direct fire.The physical properties like surface area (84.61-92.59, cm2); ratio of surface area to volume (1.01-1.27), density (0.83-1.09 g/ml), compressive force (96.57-170.8 N); and thermal properties like thermal conductivity (0.132-0.192, w/mK), specific heat (1.075-0.142, J/kg) and diffusivity (0.132-0.137, mm2/s) and Newton's cooling constant (0.49-0.54, 1/min) of the prepared cups were analyzed. The results showed that the corn cob powder can be added up to 15% (w/w) further addition reduced the physical and thermal properties of the cup.